1994
DOI: 10.1139/v94-127
|View full text |Cite
|
Sign up to set email alerts
|

Semiclassical study of sudden approximations for rotationally inelastic scattering of Ar + HF

Abstract: , 985 (1994)."Exact" quantum close coupled (CC) and infinite-order sudden approximation (IOSA) calculations have been carried out for the Ar + HF system on an accurate potential energy surface. The differential cross sections from the IOSA calculations show marked differences from the CC results. We find that the energy sudden component of the IOSA breaks down in a different manner for small and large impact parameters, significantly shifting and distorting the state-to-state differential cross sections. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Figures −4 show that the minima are N dominated, i.e., the scattering occurs mainly from the repulsive core of the potential. This is consistent with the two-state semiclassical model of refs and , which identifies a minimum in the opacity function and a trajectory deflected by the repulsive part of the potential (but accumulating net zero action), as important for interpreting the minimum in I 1 ← 0 (θ) at E / hc = 1089 cm -1 .
2 Same as Figure except for E / hc = 1089 cm -1 and the transitions (0,0) → (1,0), (0,0) → (1,1).
…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figures −4 show that the minima are N dominated, i.e., the scattering occurs mainly from the repulsive core of the potential. This is consistent with the two-state semiclassical model of refs and , which identifies a minimum in the opacity function and a trajectory deflected by the repulsive part of the potential (but accumulating net zero action), as important for interpreting the minimum in I 1 ← 0 (θ) at E / hc = 1089 cm -1 .
2 Same as Figure except for E / hc = 1089 cm -1 and the transitions (0,0) → (1,0), (0,0) → (1,1).
…”
Section: Resultssupporting
confidence: 89%
“…(1) We report accurate quantum coupled-channel (CC) scattering calculations of state-to-state and degeneracy averaged angular distributions using the Hutson potential assuming that HF is a rigid rotator. These calculations, which extend earlier work, , have been performed at eight collision energies, with the lowest one being that used in the dopplerimetry experiment of Chapman et al, while the highest one is that employed in the crossed molecular beam experiment of Rawluk et al…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…43 and 54͒ involved systems with low anisotropy of interaction, recent calculations for the collisions of He with CO and the collisions of Ar and He with OH 55-57 -systems possessing high anisotropy of interaction-showed a good agreement of the CS results with both more accurate coupled channel calculations and experimental data where available. In the case of ArϩHF collisions the CS approximation was investigated by Barrett and co-workers 58 who performed a semiclassical study of rotationally inelastic scattering on the H6 PES 37 which is similar to the PES we use in the present work. The authors 58 found that the CSA results agreed very well with their full semiclassical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of ArϩHF collisions the CS approximation was investigated by Barrett and co-workers 58 who performed a semiclassical study of rotationally inelastic scattering on the H6 PES 37 which is similar to the PES we use in the present work. The authors 58 found that the CSA results agreed very well with their full semiclassical calculations. To evaluate the error of the CSA in the present work we also perform full close coupling calculations of cross sections for multiple quantum rotational transitions in the HF(vϭ0, jϭ0)ϩAr collisions.…”
Section: Resultsmentioning
confidence: 99%